2012
DOI: 10.1371/journal.pone.0030789
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ceftazidime Resistance Mechanisms in Clinical Isolates of Burkholderia pseudomallei from Australia

Abstract: Burkholderia pseudomallei is a Gram-negative bacterium that causes the serious human disease, melioidosis. There is no vaccine against melioidosis and it can be fatal if not treated with a specific antibiotic regimen, which typically includes the third-generation cephalosporin, ceftazidime (CAZ). There have been several resistance mechanisms described for B. pseudomallei, of which the best described are amino acid changes that alter substrate specificity in the highly conserved class A β-lactamase, PenA. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
81
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 31 publications
(51 reference statements)
1
81
0
Order By: Relevance
“…3). A common feature of CAZ-resistant B. pseudomallei clinical isolates is the combination of the G-to-A mutation in the penA upstream region and mutations affecting PenA structure (16), as was also found in Bp1651.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…3). A common feature of CAZ-resistant B. pseudomallei clinical isolates is the combination of the G-to-A mutation in the penA upstream region and mutations affecting PenA structure (16), as was also found in Bp1651.…”
Section: Discussionmentioning
confidence: 70%
“…This mutation changed a putative weak Ϫ10 sequence (5=-TACGCT-3=) that is present in B. pseudomallei strains such as K96243 and 1026b to 5=-TACACT-3=, a sequence that is closer to consensus (TATAAT). The G-78A SNP has been identified in several CAZ-resistant clinical isolates (16,22). In a laboratory-selected CAZ-resistant Burkholderia thailandensis mutant, this mutation leads to increased penA transcription (18).…”
Section: Figmentioning
confidence: 99%
“…In some parts of the world, melioidosis is characterized by a 20 to 50% mortality rate with treatment, and the death rate increases to Ͼ80% for patients with sepsis (2,3). Resistance to ceftazidime is common in clinical isolates of B. pseudomallei and is linked to increased expression of serine ␤-lactamases (classes A and D) and expression of different isoforms of the class A ␤-lactamase, as well as to deletion of penicillin binding protein 3 (⌬PBP3) (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Although still rare, ceftazidime resistance as a result of therapy has been observed (7). Ceftazidime-resistant mutants are the consequence of mutations affecting the expression or amino acid sequence of chromosomally encoded class A PenA ␤-lactamase (8)(9)(10)(11)(12) and deletion of the ceftazidime target penicillin binding protein 3 (PBP3) BPSS1219 (13). However, PenA is the dominant player in ceftazidime resistance.…”
mentioning
confidence: 99%
“…While ceftazidime is a poor substrate for wild-type PenA, point mutations causing amino acid substitutions in several of the Ambler domains result in an enzyme bestowing significant ceftazidime resistance. Previously documented amino acid changes implicated in ceftazidime resistance in clinical isolates include C69Y and P167S (8,9,11,12), but other mutations continue to be identified. We previously demonstrated that PenA is secreted by the twin arginine translocation (TAT) system and that the enzyme was located in the spheroplastic fraction rather than the periplasmic fraction (10).…”
mentioning
confidence: 99%